2019
DOI: 10.11114/jets.v7i4.4150
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Unilateral and Bilateral Foot Dominance on Sprinting Speed of Young Athletes

Abstract: Purpose: Footedness as a predictor of brain hemispheric dominance cause performance differences in movement and sports performance. This study aimed to investigate the 30 m sprint speed difference between unilateral and bilateral foot dominance in 156 male and 37 female athletes.Material Method: It was assumed that all participants exerted maximum effort during 30 m sprint test in the entrance examination for schools of physical education and sports. The participants with right and left foot dominance were acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…These findings are not supported by Fisekcioglu (2011) who reported that in terms of simple Auditory Reaction time, left -handed taekwondo players perform better than right -handed ones. Selç uk et al, (2019) found that bilateral footed males were 2.81% faster than unilateral footed males. Researchers (Grace et al 1984) have shown that the current dominant and non-dominant leg force difference in athletes greater than 10% may cause injury.…”
Section: Discussionmentioning
confidence: 93%
“…These findings are not supported by Fisekcioglu (2011) who reported that in terms of simple Auditory Reaction time, left -handed taekwondo players perform better than right -handed ones. Selç uk et al, (2019) found that bilateral footed males were 2.81% faster than unilateral footed males. Researchers (Grace et al 1984) have shown that the current dominant and non-dominant leg force difference in athletes greater than 10% may cause injury.…”
Section: Discussionmentioning
confidence: 93%
“…The fact that initial practice of a motor task with one body side leads to subsequent performance with the other body side was shown in many studies that investigated upper limb [11][12][13] and lower limb movements 1,14 . However, only a few studies investigated bilateral practice of sports skills for the lower extremities or included experienced athletes especially in team sports, and the few studies that were found indicate inconsistent results 15,16 .…”
Section: Introductionmentioning
confidence: 99%